National Athletic Trainers' Association position statement: Management of asthma in athletes - Miller, M. G.; Weiler, J. M.; Baker, R.; Collins, J.; D'Alonzo, G. (Journal of Athletic Training, 2005)
Objective: To present guidelines for the recognition, prophylaxis, and management of asthma that lead to improvement in the quality of care certified athletic trainers and other heath care providers can offer to athletes with asthma, especially exercise-induced asthma.